Employee Creativity and Organizational Support as Determinants of Innovative Work Behavior at Poliwangi - Riyanto, Arif Agus Fajar; Apriono, Markus; Prihatini, Dewi (Universitas Sarjanawiyata Tamansiswa, 2025)
Innovative work behavior is a necessity for every organization to be able to adapt and solve problems effectively. This study aims to examine and analyze the influence of employee creativity and perceived organizational support on innovative work behavior among Civil Servant Educators at Banyuwangi State Polytechnic (Poliwangi), Banyuwangi Regency, East Java. This study employs a quantitative approach. The sampling technique used is non-probability sampling with a saturated sampling method. The population consists of a homogeneous category, with a sample size of 138 individuals. Data were collected through a survey technique using a questionnaire distributed to the Civil Servant Educators at Poliwangi. The data analysis technique employed is partial least squares structural equation modeling (PLS-SEM). The results of the study indicate that employee creativity and perceived organizational support have a positive and significant effect on innovative work behavior in Poliwangi. The development of employee creativity can be improved through training, workshops, and collaboration between colleagues. Fresh ideas in each individual will encourage greater innovation. Organizational support can be done by increasing trust, internal communication, and work environment support will increase innovative work behavior. Innovative work behavior produces a proactive, adaptive, and solution-oriented mindset.